2003
DOI: 10.1152/ajpheart.00708.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cell death during ischemia: relationship to mitochondrial depolarization and ROS generation

Abstract: . Cell death during ischemia: relationship to mitochondrial depolarization and ROS generation. Am J Physiol Heart Circ Physiol 284: H549-H558, 2003. First published October 10, 2002 10.1152/ajpheart.00708.2002.-Ischemia-reperfusion injury induces cell death, but the responsible mechanisms are not understood. This study examined mitochondrial depolarization and cell death during ischemia and reperfusion. Contracting cardiomyocytes were subjected to 60-min ischemia followed by 3-h reperfusion. Mitochondrial mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
3
9

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(158 citation statements)
references
References 40 publications
6
140
3
9
Order By: Relevance
“…However, other cells may not exhibit such rapid and high sensitivity to hypoxia. For example, more severe and prolonged hypoxia treatments may be necessary to induce mitochondrial depolarization in cardiomyocytes (45). Notwithstanding, our results with dopamine-containing PC12 cells confirm the conclusions of previous studies in other systems that hypoxia depolarizes ⌬⌿ m , as demonstrated by using different voltage-sensitive dyes (44,45), and that hypoxia increases the overall cellular ROS level before the onset of reperfusion (6,31,46).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, other cells may not exhibit such rapid and high sensitivity to hypoxia. For example, more severe and prolonged hypoxia treatments may be necessary to induce mitochondrial depolarization in cardiomyocytes (45). Notwithstanding, our results with dopamine-containing PC12 cells confirm the conclusions of previous studies in other systems that hypoxia depolarizes ⌬⌿ m , as demonstrated by using different voltage-sensitive dyes (44,45), and that hypoxia increases the overall cellular ROS level before the onset of reperfusion (6,31,46).…”
Section: Discussionsupporting
confidence: 89%
“…This mitochondrial sequence is present in many mammalian MSRA orthologs (16). Because mitochondria are likely to contribute to the hypoxia͞reoxygenation-mediated increase in ROS (6,44,45), preferential localization of at least some MSRA in or near mitochondria is consistent with this enzyme functioning to repair any oxidative damage in this organelle.…”
Section: Discussionmentioning
confidence: 92%
“…We found that Arg þ subjects have higher serum levels of cardiac Troponin I and CK-MB, two qualitative/quantitative markers for the extent of the ischaemic damage at the myocardial level. 38 This finding can be better understood by taking into account that hypoxia-induced cell death mediates an oxidative stressinduced damage at the mitochondrial level in cardiomyocytes, 42 and it induces the targeting of p53 to the mitochondrion. 2 Moreover, it is known that p53 activates mitochondrialdependent death pathway in ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Significant and irreversible decrease in the mitochondrial membrane potential during ischemia and oxidative stress in cardiomyocytes was reported (15). To investigate the mechanism of rescue effect by prohibitin, we analyzed mitochondrial membrane potential levels (A) H9c2 cells were fractionated using differential centrifugation method.…”
Section: Analysis Of Mitochondrial Membrane Potential Levels During Hmentioning
confidence: 99%
“…Although the reason for the difference is unclear, it may be derived from the difference of experimental conditions, hypoxia or H 2 O 2 . Mitochondrial electron transport chain increases in generation of reactive oxygen species in response to hypoxia despite the conditions of low O 2 concentration (11,15). It is proposed that hypoxia induces increase in superoxide generation in the mitochondrial matrix, which can be converted to H 2 O 2 by Mn-superoxide dismutase (5).…”
Section: Effects Of Prohibitin Overexpressin On Bcl-2 and Bax Expressmentioning
confidence: 99%